Generation of a DNA-Launched Reporter Replicon Based on Dengue Virus Type 2 as a Multipurpose Platform (2023)
Dengue viruses (DENV) have become the most important arthropod-borne viruses, causing dengue and severe dengue fever in at least 50-100 million cases each year, mainly in tropical and subtropical countries. During recent years, important advances in the molecular biology concerning the life cycle of these viruses have allowed the manipulation and generation of recombinant viruses and replicons with multiple applications, mainly in viral biology and the screening of antiviral compounds. In the present study, we describe the construction of an enhanced green fluorescent protein-bearing DENV replicon under the control of the cytomegalovirus immediate early promoter. Following a rational in silico design and cloning by standard molecular biology techniques, a reporter DENV-2 replicon and a replication-deficient mutant were constructed, and characterized by confocal microscopy and real-time RT-PCR. The results showed successful transcription, translation, and autonomous viral RNA replication of the DENV replicon from its DNA clone. This novel DENV replicon will allow the study of viral replication and testing of antiviral candidates without the need for in vitro transcription. © 2017 S. Karger AG, Basel.